1990
DOI: 10.1203/00006450-199012000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Energy Expenditure and Deposition of Breast-Fed and Formula-Fed Infants during Early Infancy

Abstract: ABSTRACT. The energy intake, expenditure, and deposition of 40 breast-fed and formula-fed infants were investigated at 1 and 4 mo of age to explore possible differences in energy utilization between feeding groups. Energy intake was calculated from 5-d test-weighing records or pre-and postweighing of formula bottles, in combination with bomb calorimetry of the milks. Total daily energy expenditure (TDEE) was determined by the doubly labeled water method. Sleeping metabolic rate (SMR) and minimal observable ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(67 citation statements)
references
References 8 publications
1
65
1
Order By: Relevance
“…Butte et al (1990) compared sleeping metabolic rate in breast-and formula-fed babies and found higher values in the latter group. The same author also found differences in sleep organisation between formula or breast-fed infants (Butte et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Butte et al (1990) compared sleeping metabolic rate in breast-and formula-fed babies and found higher values in the latter group. The same author also found differences in sleep organisation between formula or breast-fed infants (Butte et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In line with these differences in growth is the finding that energy requirements of breast-fed infants are different from those who are bottle-fed (Butte et al, 1990;Butte, 1996), and there is substantial evidence that recommendations of energy requirements (WHO, 1985) overestimate the needs by 9-39% (Butte, 1996). Energy requirements have originally been based on measurements of energy intake (WHO, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The growth discrepancy between different feeding groups of infants was discussed recently by Dewey (1998a). The breast-fed infants self-regulate their energy intake at a lower level than formula-fed infants, which has been related partly to lower metabolic rate and less weight gain (Butte et al, 1990;Davies, 1992). Other factors, such as varying digestibility and the composition of newly synthesized tissues, may differ between the feeding groups (Butte et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The breast-fed infants self-regulate their energy intake at a lower level than formula-fed infants, which has been related partly to lower metabolic rate and less weight gain (Butte et al, 1990;Davies, 1992). Other factors, such as varying digestibility and the composition of newly synthesized tissues, may differ between the feeding groups (Butte et al, 1990). It seems therefore that breast-feeding is an independent factor leading to lower energy expenditure and intake for a certain period in infancy.…”
Section: Discussionmentioning
confidence: 99%
“…In practice resting metabolic rate is usually measured under similar conditions except that the measurement is taken 4 h after a light meal. Due to practical and ethical considerations a resting fasting state cannot be attained in frequently fed infants and a SMR is measured instead (Azaz et al, 1992;Butte et al, 1990). As most of the subjects in the 0 -3-y-old age group in the studies Schofield used to predict BMR were either sleeping or sedated during testing it is expected that measured SMR in this study will equal predicted BMR.…”
Section: Comparison Of Smr and Bmr Ca Reichman Et Almentioning
confidence: 99%